What is the optimal first-line regimen for advanced non-small cell lung cancer patients with epidermal growth factor receptor mutation: a systematic review and network meta-analysis - Wengang Zhang; Xinyu Zhang; Wencheng Zhao; Zhiyi Guo; Xinyue Liu; Li Ye; Zhimin Chen; Kandi Xu; Yujin Liu; Hao Wang; Lishu Zhao; Qianqian Zhang; et al. (BMC Pulmonary Medicine)
Abstract Objectives There are currently various tyrosine kinase inhibitor (TKI)-based regimens available, and it can be challenging for clinicians to determine the most effective and safe option due to the lack of direct comparisons between these regimens. In this study, we conducted a network meta-analysis comparing the efficacy and safety of distinct regimens to determine the optimal regimen for patients with EGFR-mutated non-small cell lung cancer, thereby facilitating clinical decision-making. Materials and methods The PubMed, Embase, Cochrane Library databases and international conference databases were comprehensively searched from their inception to 02 April 2024 for collecting data regarding efficacy and safety from eligible randomized controlled trials (RCTs). Following literature screening and data extraction, a NMA was conducted to compare the efficacy and safety among 21 regimens with a random-effects consistency model in a Bayesian framework using a Markov Chain Monte Carlo simulation technique within the GEMTC package. Results A total of 35 RCTs were included, involving 9718 individuals and 21 regimens. Compared with other interventions, combination therapies based on third-generation TKIs, especially osimertinib plus ramucirumab, showed the most favorable PFS prolongation in overall patients. Consistently, subgroup analyses showed that third-generation TKIs-based combination regimens were superior to other regimens in most prespecified subgroups with distinct clinicopathological characteristics. In terms of overall survival, despite the combination regimens based on third-generation TKIs also showing relatively superior outcomes, erlotinib plus chemotherapy and gefitinib plus chemotherapy were ranked more favorably. In terms of safety profile, combination therapies based on third-generation TKIs did not significantly increase the incidence of grade 3 or higher adverse events compared with other regimens. Conclusion Our study concluded that combination regimens based on third-generation TKIs (osimertinib plus ramucirumab, osimertinib plus chemotherapy, osimertinib plus bevacizumab, amivantamab plus lazertinib and aumolertinib plus apatinib) could be the new and clinically preferable first-line, standard of care for EGFR-mutated advanced non-small cell lung cancer. Trial registration The protocol was registered in the Prospective Register of Systematic Reviews (PROSPERO CRD42023480596).